Covid-19 Pandemic and the Freedom-Security Tension: Calibrating their Fragile Relationship - Méndez, Pablo Martín (2023)
Grounded in a will to adapt to dangers, and espouse both responsibility and resilience, voluntary measures have largely replaced one of the oldest public health strategies, quarantine. The Covid-19 pandemic, however, elicited a broad sweep of tactics from the archive of public health armoury. On a general level, this review essay addresses the common measures rolled out by various authorities against the pandemic - the lock-downs, reopening process, financial support and vaccination. By relating these measures to 1) the "plague-stricken town", deployed during the seventeenth and eighteenth centuries in Europe by the Polizeistaat; 2) the "self-regulation strategy" that emerged with liberal ideas at the end of the eighteenth century; and 3) the "minimum security" programmed by neoliberal governmentality in the second half of the twentieth century, it is suggested that tensions between freedom and security during, and after, the pandemic can be better understood. To end, the essay noticed that the pandemic has enforced tensions in the administration and calibration of individual wishes and collective wellbeing, creating a fragile “freedom-security relationship” and new problem space for self-regulation.